The Value of Central Clearing - VUILLEMEY, GUILLAUME (Journal of Finance, 2020)
ABSTRACT I study a contracting innovation that suddenly insulated traders of hedging contracts against counterparty risk: central clearing counterparties (CCPs) for derivatives. The first CCP was created in Le Havre (France) in 1882, in the coffee futures market. Using triple difference‐in‐differences estimation, I show that central clearing changed the geography of trade flows Europe‐wide, to the benefit of Le Havre. Inspecting the mechanism using trader‐level data, I find that the CCP solved both a “missing market” problem and adverse selection issues. Central clearing also facilitated entry of new traders in the market. The successful contracting innovation quickly spread to other exchanges.